An analysis of the OPEC Reference Basket with regards to African Pricing and Spread to the WTI and Brent - Awasom, Nde-Asaa (Department of Finance and Tax, 2020)
This study aims at analysing how African oil benchmarks within the OPEC Reference Basket relative to the WTI and Brent benchmarks which are considered as global pricing benchmarks for the period starting from 1997-2008. The Nigerian Bonny Light and Algerian Saharan blend were the two benchmarks used for this study. A time series analysis was applied to the weekly price data series set and with the aid of a breakpoint unit root test and Cusum of Squared test to determine if there was a change in the persistence of the spread of each African benchmark relative to the global benchmarks. The results for from the unit root test indicated the presence of a structural break in the price spread in 2004 for the Bonny Light benchmark and in 2005 for the Saharan blend relative to both global benchmarks. The Cusum Squared test for the four benchmark pairings indicated a change in persistence of the price spreads. The null hypothesis was rejected for the alternative hypothesis of the price spread process having a relatively high persistence value after a while. The Cusum Test results showed a change in persistence for both African benchmarks relative to the WTI benchmark and no change in persistence relative to the Brent benchmark. The results of from the Time series analysis indicated the competitive nature of African benchmarks relative to global benchmarks and this could benefit exporting countries by virtue of setting up derivative markets. The derivative markets would allow for the trade of benchmark spreads, futures contracts, options and other financial instruments for African oil producers.